Bilosomal Co-Encapsulated Tamoxifen and Propranolol for Potentiated Anti-Breast Cancer Efficacy: In Vitro and In Vivo Investigation - Toka T. Elebyary; Amal A. Sultan; Sally E. Abu-Risha; Gamal M. El Maghraby; Manna Amin (Pharmaceutics)
Background/Objectives: Tamoxifen (TAM) is an anti-breast cancer drug suffering from acquired resistance development, prompting cancer relapse. Propranolol (PRO)’s repurposing for cancer therapy has gained interest. This work aimed to investigate combined TAM/PRO therapy for potentiating the anti-breast cancer activity of TAM. The work probed bilosomes versus standard noisome for simultaneous oral and intratumor delivery of TAM and PRO. Methods: Bilosomes comprising Span60, cholesterol, and increasing concentrations of bile salts were prepared together with bile salts containing free standard niosomes. The vesicular size and morphology were characterized. The entrapment and release efficiencies of TAM and PRO from the tailored vesicles were determined. The in vivo investigations of anti-tumor activity of TAM with or without PRO employed the solid Ehrlich carcinoma model. Results: The vesicles of all fabricated dispersions were spherical and negatively charged, with a size ranging from 104 to 182 nm. The entrapment efficiency depended on the nature of the drug, recording values ranging from 87.5% to 97.8% for TAM and from 31.0% to 46.8% for PRO. Incorporation of bile salts into vesicles increased TAM and PRO release compared to standard niosomes. Oral administration of combined TAM/PRO bilosomes showed a significant reduction in tumor growth volume compared to that recorded following naked drug administration. Histopathological investigations reflected a significant decline in tumor giant cells and mitotic figures, implying the in vivo capability of the TAM/PRO combination to interfere with cancer cell proliferation and persistence. Conclusions: The overall results demonstrated the impact of repurposed PRO to enhance the anti-breast cancer activity of TAM when both were co-encapsulated into bilosomes.